Performance Assessment of Nepalese Banks Based on Learning and Growth Perspective - Parajuli, Dilip (Butwal Campus Journal, 2020)
The purpose of this paper is to assess performance of Nepalese banks under the learning and growth perspective of the BSC model and to study comparative status of learning and growth in three types of banks - the state owned, private and joint venture banks. This paper follows descriptive research design approach. The questionnaire survey has been applied as primary tool for collecting required information and 466 responses were collected from bank managers. To assess the responses to the BSC model's learning and growth perspective, a five-point Likert-type scale of strongly disagree (1) to strongly agree (5) has been used. The findings of study have indicated that joint venture banks stood at top, state owned banks in second and private banks in the bottom to adopt learning and growth perspective performance. The descriptive analysis has shown satisfactory status of the banks. Among the fourteen items used for assessment of learning and growth performance, improving employee capabilities, teamwork, and better culture and leadership were more emphasized areas by the banks to enhance learning and growth performance.